A comprehensive gene–environment interaction analysis in Ovarian Cancer using genome‐wide significant common variants. Issue 9 (20th January 2019) - Kim, Sehee; Wang, Miao; Tyrer, Jonathan P.; Jensen, Allan; Wiensch, Ashley; Liu, Gang; Lee, Alice W.; Ness, Roberta B.; Salvatore, Maxwell; Tworoger, Shelley S.; Whittemore, Alice S.; Anton‐Culver, Hoda; et al.
Abstract : As a follow‐up to genome‐wide association analysis of common variants associated with ovarian carcinoma (cancer), our study considers seven well‐known ovarian cancer risk factors and their interactions with 28 genome‐wide significant common genetic variants. The interaction analyses were based on data from 9971 ovarian cancer cases and 15, 566 controls from 17 case–control studies. Likelihood ratio and Wald tests for multiplicative interaction and for relative excess risk due to additive interaction were used. The top multiplicative interaction was noted between oral contraceptive pill (OCP) use (ever vs . never) and rs13255292 ( p value = 3.48 × 10 −4 ). Among women with the TT genotype for this variant, the odds ratio for OCP use was 0.53 (95% CI = 0.46–0.60) compared to 0.71 (95%CI = 0.66–0.77) for women with the CC genotype. When stratified by duration of OCP use, women with 1–5 years of OCP use exhibited differential protective benefit across genotypes. However, no interaction on either the multiplicative or additive scale was found to be statistically significant after multiple testing correction. The results suggest that OCP use may offer increased benefit for women who are carriers of the T allele in rs13255292. On the other hand, for women carrying the C allele in this variant, longer (5+ years) use of OCP may reduce the impact of carrying the risk allele of this SNP. Replication of this finding is needed. The study presents a comprehensive analytic framework for conducting gene–environment analysis in ovarian cancer. Abstract : What's new? Genetic and environmental risk factors for ovarian cancer have been identified separately but interactions between both remain largely unexplored. The authors identified a new gene x environment interaction between oral contraceptive pill (OCP) use and a single nucleotide polymorphism in the PVT1 gene, a long‐noncoding RNA located on chromosome 8. The data suggest that the protective benefit of OCP use may be strongest in women with the T allele of PVT1 underscoring the need to tailor prevention strategies to individual genotypic profiles.